The Role of PPARγ in Helicobacter pylori Infection and Gastric Carcinogenesis - Jong-Min Lee; Sung Soo Kim; Young-Seok Cho (PPAR Research)
Peroxisome proliferator-activated receptor γ (PPARγ) is a nuclear receptor that is important in many physiological and pathological processes, such as lipid metabolism, insulin sensitivity, inflammation, cell proliferation, and carcinogenesis. Several studies have shown that PPARγ plays an important role in gastric mucosal injury due to Helicobacter pylori (H. pylori). As H. pylori infection is the main etiologic factor in chronic gastritis and gastric cancer, understanding of the potential roles of PPARγ in H. pylori infection may lead to the development of a therapeutic target. In this paper, the authors discuss the current knowledge on the role of PPARγ in H. pylori infection and its related gastric carcinogenesis.